The recruitment and selection of young managers by British business 1930-2000 - Hicks, M; Michael Edward Hicks (2004)
A pervasive critique argues that the educational and social background of senior managers, determined largely by recruitment policies and practices, was an important contributor to the relative economic decline of Britain. The current thesis argues that this critique, even in nuanced form, suffers from serious flaws. For example, long term results of recruitment are confused with information on recruitment processes. In fact, corporate performance can only be judged by understanding the challenges that faced companies, and the limits of the options available to them. The objective of the work, then, is to outline the steps sensible recruiters should have taken to secure their needs for bright young entrants, and to describe and measure what in fact happened. Key findings are that: the criteria used by companies to define high-flier entrants – intelligence, certain personal skills, and signs of character - have remained fundamentally unchanged even if emphasis has moved. Business pursued these attributes through proxies, the most important of which was that of educational qualifications. Business was rightly slow, until the 1950s, to recruit graduate entrants because most bright young people did not attend university. Although British peculiarity in terms of non-vocationalism has been exaggerated, a lesser focus on ‘relevant’ qualifications for non-technical positions was not an economic disadvantage. Proxies for personal qualities were less robust but, over time, were replaced by better direct measurement of individual qualities. The solution found in Britain to bring educated young people together with employers through regional and national recruitment institutions, including the graduate milkround, has proven highly successful. The selection of entrants has been approached at least as well as abroad, and notably unreliable tools were avoided. Business obtained an ever growing proportion of young talent, and did so by integrating educated young people from new social strata to an extent unmatched abroad.